Pengaruh Audio Suara Kucing terhadap Intensitas Serangan Hama Tikus (Rattus spp.) di Pertanaman Jagung (Zea Mays L.) - Fita Fitriatul Wahidah; Rahmah Arfiyah Ula; Sitti Nur Ilmiah; Lilik Erviani; Merinda Nur Indahsari; Nabilatul Hamidah (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
Continuous chemical control of rat pests (Rattus spp.) can sometimes lead to resistance and resurgence problems, and even some cases of inaccurate targeting ultimately killing livestock. The idea of ​​​​repelling rats in rice fields using vibrations of crickets and other natural animals transmitted via radio has been done and the results are quite optimal for rat control, but it has not been done in corn cultivation. The purpose of this study was to determine the effect of cat sound audio on the intensity of rat pest attacks (Rattus spp.) in corn (Zea mays L.) plantations. The research location was in a farmer's land owned by a farmer in Dagan Village, Solokuro District, Lamongan Regency. Determination of sampling points using the diagonal method, each into 5 sub-observation plots. In each sub-plot, markers were placed as sampling points. Audio with cat and bird sounds was played continuously from 05.00 pm - 07.00 am. Observations were conducted at 7:00 a.m. at all sampling points at 30 and 60 days after planting. Observations were conducted for three days using audio and three days without audio. Damage symptoms were observed directly at each sampling point. Corn plants showing symptoms were then recorded and analyzed using the Damage Intensity formula. Observations showed that the use of cat sound audio was able to reduce the level of rat infestation. At 30 days after planting, the damage percentage was reduced by 8.33%. Meanwhile, at 60 days after planting, the damage percentage was reduced by 18.33%.